PERILAKU KREATIF DAN INOVATIF PENGRAJIN SEPATU KULIT DI DUSUN GENENGAN KABUPATEN MOJOKERTO - Hesti Wiyatmi Wulandari; Bambang Suyadi (Economic Education, University of Jember, 2015)
This research was used to describe the behavior of creative and innovative craftsman of leather shoes in Dusun Genengan Kabupaten Mojokerto to compete and follow the development of the needs of market . Purposive method was used in this research to decide the subject of this research. The research area was chosen by purposive area that was Dusun Genengan Desa Banjaragung Kecamatan Dlanggu Kabupaten Mojokerto. The data collection methods of this research were interview, observation and document. The data analysis was descriptive qualitative: reducing data, presenting data and concluding data. have behavior creative and innovative in the manufacture of desaign, combination of color, and brand of leather shoes. This is shown with creative craftsman of leather shoes in Dusun Genengan Desa Banjaragung Kecamatan Puri Kabupaten Mojokerto made sample of shoes using desaign and combination of new color. Behavior innovative craftsman of leather shoes in Dusun Genengan Desa Banjaragung Kecamatan Puri Kabupaten Mojokerto made leather shoes using desaign and combination of color, and brand new and different. Reason craftsman of leather shoes in Dusun Genengan Desa Banjaragung Kecamatan Puri Kabupaten Mojokerto have behavior creative and innovative the first, make a desaign of shoes that follow the development of the needs of consumers. Second, the combination of color favored and in accordance with the needs of consumers. Third, accentuating the indentity of their leather shoes industry by the presence of leather shoes band new and defferent.